Biperiden and mepazine effectively inhibit MALT1 activity and tumor growth in pancreatic cancer. Issue 6 (25th July 2019) - Konczalla, Leonie; Perez, Daniel R.; Wenzel, Nadine; Wolters‐Eisfeld, Gerrit; Klemp, Clarissa; Lüddeke, Johanna; Wolski, Annika; Landschulze, Dirk; Meier, Chris; Buchholz, Anika; Yao, Dichao; Hofmann, Bianca T.; et al.
Abstract : MALT1 is a key mediator of NF‐κB signaling and a main driver of B‐cell lymphomas. Remarkably, MALT1 is expressed in the majority of pancreatic ductal adenocarcinomas (PDACs) as well, but absent from normal exocrine pancreatic tissue. Following, MALT1 shows off to be a specific target in cancer cells of PDAC without affecting regular pancreatic cells. Therefore, we studied the impact of pharmacological MALT1 inhibition in pancreatic cancer and showed promising effects on tumor progression. Mepazine (Mep), a phenothiazine derivative, is a known potent MALT1 inhibitor. Newly, we described that biperiden (Bip) is a potent MALT1 inhibitor with even less pharmacological side effects. Thus, Bip is a promising drug leading to reduced proliferation and increased apoptosis in PDAC cells in vitro and in vivo . By compromising MALT1 activity, nuclear translocation of c‐Rel is prevented. c‐Rel is critical for NF‐κB‐dependent inhibition of apoptosis. Hence, off‐label use of Bip or Mep represents a promising new therapeutic approach to PDAC treatment. Regularly, the Anticholinergicum Bip is used to treat neurological side effects of Phenothiazines, like extrapyramidal symptoms. Abstract : What's new? Pancreatic cancer is the fifth leading cause of cancer‐related deaths worldwide, with a five‐year survival rate of just 6 %. Thus, new therapeutic approaches are urgently needed. Here, targeting of the protein MALT1 with either biperiden or mepazine inhibited the growth of pancreatic ductal adenocarcinoma (PDAC) cells and increased PDAC cell apoptosis in vitro and in vivo . Analyses showed MALT1 to be expressed in the majority of pancreatic cancer cells, while lacking in healthy tissue. The data identify MALT1 as a novel therapeutic target in PDAC and identify biperiden and mepazine as promising therapeutic agents for the disease.